2018
DOI: 10.1080/09273972.2018.1492621
|View full text |Cite
|
Sign up to set email alerts
|

A modified vertical muscle transposition for the treatment of large-angle esotropia due to sixth nerve palsy

Abstract: This procedure is comparable to traditional procedures with the advantages of no need to tenotomy or splitting and can be a good alternative to conventional Hummelsheim's procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…29 A success rate was obtained in 20/32 (62.50%) patients with an under-correction in 12/32 (37.50%) patients, which was substantially lower than that in patients with CN VI palsy (78%-100%). 30,31 Several limitations of this study should be considered. First, as this study focused only on isolated MRP, it would not be possible to determine the incidence of MRP along with other palsies of extraocular muscles.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…29 A success rate was obtained in 20/32 (62.50%) patients with an under-correction in 12/32 (37.50%) patients, which was substantially lower than that in patients with CN VI palsy (78%-100%). 30,31 Several limitations of this study should be considered. First, as this study focused only on isolated MRP, it would not be possible to determine the incidence of MRP along with other palsies of extraocular muscles.…”
Section: Discussionmentioning
confidence: 96%
“…When medial rectus muscle repair was not possible and there was sufficient scar formation around the ruptured muscle, lateral rectus recession and medial rectus resection were also used to correct the deviation, as Chen et al's study suggested 29 . A success rate was obtained in 20/32 (62.50%) patients with an under‐correction in 12/32 (37.50%) patients, which was substantially lower than that in patients with CN VI palsy (78%‐100%) 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…It involves making radial conjunctival incision in superotemporal and inferotemporal quadrants, and it could be done with Cul-de-sac or MISS incisions. 26 The surgical correction by muscle transposition alone ranges from 24 to 36 PD, and that by muscle transposition and recession of the medial rectus muscle increases up to 62 PD. The most important feature of this procedure compared with the other procedures is that this technique is surgically more straightforward and minimal, with less damage to the ocular fascia.…”
Section: R Esultsmentioning
confidence: 99%
“…In chronic sixth cranial nerve palsies, surgery is indicated when spontaneous resolution does not take place after 6 months, 1 2 although some studies consider waiting even up to 10 months. 3 4 5 The amount of residual function of lateral rectus (LR) muscle is very important for determining the surgical plan. A simple way is to score LR function (abduction) deficiency.…”
Section: Introductionmentioning
confidence: 99%